Methods of developing stress resistance of law enforcement officers at the stage of professional training - V. V. Dotsenko (Law and Safety)
The results of theoretical analysis of modern directions, approaches and methods of stress management have been presented. It has been determined that the classification of methods of stress management depends on the type of psychotherapy, the direction of work with stress, time parameters of interaction with stress factors, the method of influencing the functional state, the method of anti-stress influence, etc. Based on the analysis of various scientific approaches, the methods of developing the ability to handle stress from law enforcers who study in higher education institutions with specific learning conditions are systematized and divided into three branches: prevention, neutralization and correction of stress, and recovery of organism resources.